Licensing acceptance in a mineral-rich welfare state: Critical reflections on the social license to operate in Sweden. Issue 3 (July 2020) - Poelzer, Gregory; Lindahl, Karin Beland; Segerstedt, Eugenia; Abrahamsson, Lena; Karlsson, Martin
Highlights: Social license to operate is a tool to address significant problems through engagement. Social license to operate is an indicator of deficiencies in the institutional and regulatory framework. A highly regulated context minimizes the room for social license to operate to maneuver. Abstract: The Social License to Operate (SLO) continues to influence industry, government, and academia on issues of resource development, particularly mining. But it risks becoming a term that includes all types of company activity aimed at gaining public support. To delimit the term, we look at the malleability of the SLO in a highly-regulated context: Sweden. Comparing the academic literature on the SLO at the global level and in the Swedish context, we assess the usefulness of the term across three themes: institutions, corporate-community engagement, and sustainability. Through this review, we argue that the SLO is best understood as a tool and an indicator. A tool to address significant problems and issues and an indicator of deficiencies in the existing institutional framework